Wittgenstein: epistemología y lenguaje - Gallardo Corrales, Andrés (2011)
The paper deals with Wittgenstein ́s ideas about epistemology and language, mainly those from his Philosophical Investigations and On Certainty, so that the relationship between this thought and current debates in contemporary epistemology can be accurately defined.